2019
DOI: 10.3390/jcm8040553
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effect of Low Dose Nefopam Hydrochloride after Arthroscopic Rotator Cuff Repair: A Randomized Controlled Trial

Abstract: Arthroscopic rotator cuff repair causes acute postoperative hyperalgesia. Multimodal analgesia is preferable to opioid-based intravenous patient-controlled analgesia (IV-PCA) due to postoperative nausea and vomiting (PONV). We evaluated the effect of nefopam as a postoperative non-opioid analgesic after shoulder surgeries. A total of 180 adult patients were enrolled for arthroscopic rotator cuff repair. They were randomly assigned to nefopam (N) or control (C) groups and each group was reclassified according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…15 Koh et al (2019) found no significant difference in demographic data. 16 Du Manoir et al (2003) also found comparable data with respect to the characteristics of the two groups of Nefopam and placebo group. 11 As per Paudel R et al (2017), there was no difference between Tramadol and Diclofenac groups in gender wise distribution of patients and majority were males.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…15 Koh et al (2019) found no significant difference in demographic data. 16 Du Manoir et al (2003) also found comparable data with respect to the characteristics of the two groups of Nefopam and placebo group. 11 As per Paudel R et al (2017), there was no difference between Tramadol and Diclofenac groups in gender wise distribution of patients and majority were males.…”
Section: Discussionmentioning
confidence: 79%
“…17 YN OH et al (2018) reported that there was insignificant difference (p = 0.48) in the VAS scores at 10 and 30 minute, and 1, 4, 8, 12, 24, and 48 hour between the nefopam and ketorolac group after surgery. 20 Koh et al (2019) documented no significant VAS score difference between the Nefopam and Control group. 16 Our study showed significant (p=0.002) difference between the groups in Verbal Rating Scale (VRS) score only at 24 hours.…”
Section: Discussionmentioning
confidence: 85%
“…However, conflicting results have also been reported, especially in surgeries anticipated to cause moderate to severe pain [ 24 , 25 , 26 , 27 ]. Cuvillon et al reported that continuous intravenous infusion of nefopam (120 mg) during the first 48 h after open colectomy did not reduce perioperative opioid consumption and produced no differences in patient satisfaction or adverse events compared with the control group [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, intraoperative administration of 40 mg of nefopam decreased pain at 6 h after laparoscopic gastrectomy, although it did not decrease pain after 6 h [ 17 ]. Postoperative administration of 20 mg of nefopam at the PACU did not reduce pain during 48 h of follow-up after arthroscopic rotator cuff surgery [ 18 ]. In our study, we initiated PCA administration at the time of skin closure.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the analgesic effect results from reduction in the neurokinin-1 receptor, which may inhibit substance P and neurokinin-1 signaling and subsequently lead to decreased nociceptive responses [ 12 ]. Nefopam has been used in several surgical procedures as an analgesic and as a component of multimodal analgesia for enhanced recovery after surgery (ERAS) [ 15 , 16 , 17 , 18 , 19 ]. However, protocols that consider the efficacy and safety, appropriate dose, administration time, administration methods (continuous or bolus injection), and combination with other drugs have not yet been identified.…”
Section: Introductionmentioning
confidence: 99%